Psychological wellbeing of Italian students and clinical assessment tools at university counseling services during the COVID-19 pandemic: a systematic review - Celia, Giovanna; Serio, Gianluigi; Trotta, Eugenio; Tessitore, Francesca; Cozzolino, Mauro (Frontiers in Psychology, 2024)
The COVID-19 pandemic brought about unprecedented problems for contemporary society. Among the numerous challenges faced following the spread of the virus, the need to provide assessment tools and remote psychological assistance certainly deserves particular attention. Indeed, this profound paradigm shift in psychological assessment and care occurred during a period of fragility for people already suffering from the restrictions imposed to stem the spread of the virus. One population particularly affected by the pandemic was students, including university students. The latter faced the pandemic in a particularly critical formative period. For these reasons, our systematic review has two main objectives: i) identify the assessment tools and psychological dimensions most used/investigated during the pandemic in Italian university students; ii) systematize and deepen our knowledge about the impact of the pandemic on the psychological well-being of Italian university students. Our search used PRISMA 2020 guidelines on Web of Science, Pubmed, Scopus, and EBSCOHost. The results indicated that the psychological dimensions most investigated in university students during the pandemic were anxiety and depression. At the same time, the most used assessment instruments were the State-Trait Anxiety Inventory (STAI-Y) and the Beck Depression Inventory-II (BDI-II). Furthermore, it is clear from the results that the pandemic has harmed the psychological well-being of university students. Finally, we dedicated a section to discuss the interventions implemented by university counseling services during the pandemic. This review could improve the work of university counseling services in this post-pandemic period and contribute to developing specific screening and assessment programs for future emergencies.